2022
DOI: 10.1155/2022/8363850
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Detection of Breast Cancer Using Histopathological Image Classification Dataset with Deep Learning Techniques

Abstract: Cancer is one of the top causes of mortality, and it arises when cells in the body grow abnormally, like in the case of breast cancer. For people all around the world, it has now become a huge issue and a threat to their safety and wellbeing. Breast cancer is one of the major causes of death among females all over the globe, and it is particularly prevalent in the United States. It is possible to diagnose breast cancer using a variety of imaging modalities including mammography, computerized tomography (CT), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Figure 7 displays the comparative evaluation of the obtained accuracy analysis between the proposed system with recent algorithms since this metric is standard in all conducted works. This graph shows that the implemented methods in [ 4 , 10 ] achieved minimal accuracies of 81% and 92.44%, respectively. Furthermore, the implemented method in [ 8 ] achieved a moderate accuracy of 96.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 7 displays the comparative evaluation of the obtained accuracy analysis between the proposed system with recent algorithms since this metric is standard in all conducted works. This graph shows that the implemented methods in [ 4 , 10 ] achieved minimal accuracies of 81% and 92.44%, respectively. Furthermore, the implemented method in [ 8 ] achieved a moderate accuracy of 96.5%.…”
Section: Resultsmentioning
confidence: 99%
“… The obtained accuracy analysis charts between the proposed system and some related work [ 1 , 2 , 3 , 4 ] and [ 7 , 8 , 9 , 10 ]. …”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…To highlight the enhanced outcomes of the CSSADTL-BCC model, a brief comparison study with recent models is shown in Table 3 [ 22 ]. Figure 11 investigates a detailed and analysis of the CSSADTL-BCC with existing models.…”
Section: Performance Validationmentioning
confidence: 99%
“…Detection is finetuned after pretraining using ImageNet. en, there is the question of whether this kind of backbone can be utilized to extract image features for target identification to maximize performance [10,[23][24][25][26]. e expense of reaching exceptional detection performance, on the other hand, would be rather significant if a new backbone was developed and pretrained on ImageNet.…”
Section: Relu (Cmentioning
confidence: 99%